Agronomic performance and adaptation of the CROPGRO - Perennial Forage Model to predict growth of three tropical forage grasses under irrigated and rainfed conditions - Pequeno, Diego Noleto Luz (2014)
Grasses of the genera Brachiaria and Cynodon are some of the most important pasture introductions in Brazil. Convert HD 364 brachiariagrass, a new Brachiaria hybrid, was released as an option for a broad range of environmental conditions, high nutritive value and forage production. Forage-based livestock systems are complex and interactions among animals, plants, and the environment exist at several levels of complexity, which can be evaluated using computer modeling. Herbage accumulation, crude protein (CP), neutral detergent fiber (NDF), in vitro organic matter digestibility (IVOMD), plant-part composition, leaf photosynthesis, leaf area index (LAI), and light interception (LI) were evaluated as affected by two harvest frequency (28 and 42-days), irrigated and rainfed in a clipping study from April 2011 to April 2013, contrasting Convert HD 364® brachiariagrass (Brachiaria hybrid CIAT 36061), Marandu palisadegrass {Brachiaria brizantha (Hochst. ex A. Rich.) R. D. Webster [syn. Urochloa brizantha (A. Rich.) Stapf]; CIAT 6297}, and Tifton 85 bermudagrass (Cynodon spp.). The experimental design for both the irrigated and the rainfed trials was a randomized complete block with four replications. Convert HD 364 had similar or higher annual herbage accumulation, seasonal yield and herbage accumulation rate than Marandu and Tifton 85, (15% more herbage accumulation than Marandu and 12% more than Tifton 85 when irrigated and when harvested at shorter regrowth intervals). Convert HD 364 had good seasonal distribution of total annual herbage produced and accumulates about 30% of the total herbage mass during the cool season in Piracicaba, similar to Marandu. Tifton 85 produced around 20% of its average annual yield during dry season. Tifton 85 forage had higher CP concentration than the other two grasses when harvested at shorter intervals and when irrigated. The NDF concentration in Convert HD 364 was lower than in the other grasses regardless of irrigation treatment, harvest frequency, and season of the year, resulting in high IVOMD (more than 650 g kg-1), similar to that of Marandu. Regard to CROPGRO calibration, in general the model performance was good for the three grasses. Leaf and stem weight simulations were improved, due to increase partitioning to stem for low harvest frequencies. The LAI and LI were well performed by the model, showing increase for lower harvest frequency, with exception to Tifton 85. Under rainfed conditions, the simulations using the Penman-Monteith-FAO 56 method gave more realistic water stress responses than using the Priestley and Taylor method. Calibration results suggest that the CROPGRO - Perennial Forage Model can be used to adequately simulate growth of Marandu, Convert HD 364, and Tifton 85 under irrigated and rainfed conditions, being able to simulate different harvest frequency managements.